&times;ž&times;ž&times;Ÿ17

&times;ž&times;ž&times;Ÿ17 - 17" 1 0 a0...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 17 " 1 . 0 , a0 = 1 , 1 1 , a1 = 2 . 1 : 2 2 , a2 = 7 :1 , , . 7 " . 4 , . n an . an -1 - , n - 1 , , , an - 2 - , n - 2 . . n > 2 , an = 2an -1 + 3an - 2 , n , . a0 = 1, a1 = 2 2 - , . , a2 = 2a1 + 3a0 = 7 n : an = . an = 2an -1 + 3an - 2 .1 , ) ( .2 n = 2 n -1 + 3 n - 2 : n - 2 - 2 - 2 - 3 = 0 . 3n (- n : . an = A + B 1) . 1 = 3, 2 = -1 , n = 0 a0 = 1 A + B = 1 n = 1 a1 = 2 3 A - B = 2 : an . B = 1 3 - A = , 4 4 an = 3 n 1 3n +1 + (-1) n + 1) n = 3 (- 4 4 4 : a4 .3 a4 = 35 + 1 = 61 4 : a 2 = 7 a 3 = 2a2 + 3a1 = 20 a4 = 2a3 + 3a2 = 61 . 2 0 - , x1 + x2 + x3 + x4 + x5 + x6 = 29 ,15 " .- , , 1 . ( ) = 20 6 3 , : x 29 f ( x) = ( x 2 + x 4 + x 6 K)3 ( x3 + x 5 + x 7 K)3 = x15 (1 + x 2 + x 4 K)6 = : , y = x 2 : (1 + x + x K) - x14 2 4 6 = (1 + y + y 2 K)6 = : , y 7 1 (1 - y )6 x14 ." (iii ) + D(6, 7) = ( 6-61-17 ) = ( 12 ) = 792 5 - , x1 + x2 + x3 + x4 + x5 + x6 = 29 20 . 792 = 15840 , 20 3 : x k , .1 (1 + x + x 2 )(1 + x) n = (1 + x) n + x(1 + x) n + x 2 (1 + x) n , ( ) n k -1 x k -1 ,( ) ( ) n k (1 + x) x k n x k . . n k n k -1 ( ) n k -2 n k -2 x k - 2 n k n +1 k -1 ( ) +( ) +( ) =( ) +( ) : x16 .2 5x2 - x 4 = (5 x 2 - x 4 )(1 + x + x 2 K)3 = 5 x 2 (1 + x + x 2 K)3 - x 4 (1 + x + x 2 K)3 3 (1 - x) x12 , D(3,14) = ( 3-1+14 3-1 ) = ( ) = 120 16 2 (1 + x + x K) - x14 2 3 x16 . D(3,12) = ( 3-1+12 3-1 ) = ( ) = 91 14 2 120 . 5 - 91 = 509 4 (1 + x) n (1 - x) n = (1 - x 2 ) n : . m , (1 + x) = n n k =0 ( )x n k n n k . (1 + x) , (1 - x ) n n , . (1 - x) = ( ) ( -x ) k =0 n k k = n ) (-1) k x k (k k =0 , (-1) m-k = (-1) 2b k m - , , m k =0 ( )( n k n m-k ) (-1) m-k (1 + x ) n (1 - x ) n - x m m k =0 . k =0 ( )( n k n 2b -k ) (-1)k , m = 2b . 2 n n k n k ( )( n k n m -k ) (-1) k . (1 - x ) = ( ) (- x 2 k ) = k ) (-1) k x 2 k , (n k n . ( b ) (-1) x m = x 2b n b : x m , 2b k =0 ( )( n k n 2b -k ) (-1) = ( ) (-1) k n b b b ) ( :( b = 2 ) n = 3, m = 4 4 k =0 ( ) ( ) (-1) = ( ) (-1) 3 k 3 4-k k 3 2 2 -3 + 9 - 3 = 3 . . 3 (1 - x 2 )3 = 1 - 3 x 2 + 3x 4 - x 6 - x 4 ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online